Energy Balance, Cost and Architectural Design Features of 24 Building Integrated Photovoltaic Projects Using a Modelling Approach - Cihan Gercek (Applied Sciences, 2020)
This paper presents the energy balance, architectural design features and cost aspects of 24 building integrated photovoltaic (BIPV) projects in three different contexts, namely BIPV in residential, office and historical buildings. These BIPV projects have been modelled and evaluated for different geographic locations because the European Energy Performance of Buildings Directive (2018/844/EU) has resulted in country-specific regulations and situations aimed towards the reduction in energy consumption, and hence the CO2 emissions of built environments. Moreover, the geographical variation of irradiation affects the performance of different BIPV projects on different locations. The results of our study show that the return of investment of BIPV projects across 12 countries took (on average) 13.3 years. Furthermore, the residential projects —as compared to non-residential buildings— were mostly energy plus buildings with an average self-sufficiency of 110% due to their low energy consumption. In conclusion, most BIPV projects resulted in realistic energy performances (on average: 761 kWh/kWp.year), low payback times (10 years for residential and office buildings), and modelled unique design features.